Analysis of Factors Affecting the Income of Tidal Swamp Rice Farming in the OPLA Program in Merah Mata Village Banyuasin I District Banyuasin Regency : Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Padi Lahan Rawa Pasang Surut Pada Program OPLA di Desa Merah Mata Kecamatan Banyuasin I Kabupaten Banyuasin - Muhammad Novriansyah Kurniawan; Riswani (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2026)
The Swamp Land Optimization Program (OPLA) is a program established by the Ministry of Agriculture in 2019 with the aim of optimizing the use of lowland swamp and tidal swamp land through the management of agricultural land, construction of embankments, subsidies for new superior rice seed varieties (VUB), as well as increasing the cropping index. The problem formulation in this study is (1) How is the effort to optimize the use of tidal swamp land for rice farming activities through the implementation of the OPLA program in Merah Mata Village, Banyuasin I District, Banyuasin Regency, (2) What is the amount of income, the feasibility of rice farming, and the comparison of rice farming income on tidal swamp land before and after the OPLA program in Merah Mata Village, Banyuasin I District, Banyuasin Regency, (3) What factors influence the income of rice farming on tidal swamp land under the OPLA program in Merah Mata Village, Banyuasin I District, Banyuasin Regency. The research method used a survey method by observing field conditions, collecting data, and obtaining the required information through interviews with farmer respondents in Merah Mata Village. The data processing method in this study used a descriptive approach, calculation of rice farming income, and multiple linear regression analysis. The results obtained from this study are (1) Efforts to optimize tidal swamp land in Merah Mata Village through the OPLA program with the construction of embankments to slow the flow of tidal water, distribution of Inpari 49 Jembar rice seeds that are resistant to waterlogging, subsidies for tractor and combine harvester machines, subsidies for dolomite lime to reduce soil acidity, as well as increasing the cropping index from CI 100 to CI 200, (2) The average rice farming income before the OPLA program was Rp13,285,550, after the OPLA program of Rp18,839,594 per planting season, the business feasibility analysis of rice farming through the R/C ratio before OPLA program was 1.8 and the B/C ratio was 0.8, while after OPLA program it resulted in an R/C ratio of 2.2 and a B/C ratio of 1.2. The comparison of income through the paired sample t-test with a Sig. (2-tailed) value of 0.017 < 0.05 indicates that there is a difference in income before and after the OPLA program. (3) Positive factors that affect the income of rice farming in tidal swamp land under the OPLA program are production costs and production quantity, while land area, education level, and farming experience have a negative effect.